MORPHOLOGICAL, ANATOMICAL, AND PHYSIOLOGICAL CHANGES DURING SEED MATURATION OF SUGAR PALM (Arenga pinnata Merr.) - Aswaldi Anwar; Dini Hervani; Dede Suhendra; Muhammad Parikesit Wisnubroto; Afrima Sari (Indonesian Journal of Forestry Research, 2026)
Arenga pinnata (sugar palm) seeds are classified as seeds that have a long dormancy period. This dormancy can be influenced by the maturity level of the sugar palm fruit. This study aims to characterize the morphology and anatomy at various levels of fruit maturity and its relationship to the dormancy of sugar palm seeds. The research was conducted descriptively, involving data collection through morphological, anatomical, and physiological observations of sugar palm fruits and seeds randomly selected from productive sugar palms in Nagari Andaleh Baruh Bukik, Sungayang Subdistrict. The sampling technique was conducted through the purposive sampling method on 12 productive palm trees aged 10 years and above. The results showed that morphologically, there were changes in the color of the skin of the palm fruit to yellowish when it reached physiological maturity, as well as the texture of the hardened seed shell. Changes did not follow these changes in shell color and seed size. Physiologically, there is an increase in gibberellin hormone levels along with the increase in fruit maturity, and it continues to increase when entering the germination phase. Anatomically, the structure of the seed embryo does not show significant changes since the beginning of the fruit ripening. Based on this, there is a mutual relationship between the morphological and physiological characteristics of the dormancy of sugar palm seeds. The riper the palm fruit is, the harder the seed shell is, so the seed dormancy becomes longer and is known as morphophysiological dormancy.